Dinamika Pengembangan Kurikulum Pendidikan Diniyah Di Madrasah Nurul Jadid Angsokah Barat Palengngaan Pamekasan - Suhud, Mohammad; Maimun, Maimun (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
This study aims to illustrate the dynamics of curriculum development in early childhood education at Madrasah Nurul Jadid in Angsokah Barat, Palengaan, Pamekasan. The focus of the research includes an analysis of curriculum policies, implementation, as well as the challenges and strategies encountered in the curriculum development process. Employing a qualitative research method with a case study approach, data were collected through observations, in-depth interviews with various stakeholders, including the madrasa management, teachers, and students, as well as document analysis of the curriculum. The findings reveal that the development of the early childhood education curriculum at Madrasah Nurul Jadid has undergone several dynamics influenced by both internal and external factors. Internal dynamics include changes in student needs and efforts to adjust the curriculum to meet these needs, such as enhancing teacher capacity through training and workshops. External dynamics encompass changes in national education policies that require madrasas to continually adapt their curricula, along with financial challenges impacting the procurement of facilities and teaching materials. Strategies employed by Madrasah Nurul Jadid to address these challenges include collaboration with other institutions to gain resource support, developing a flexible and adaptive curriculum in response to changes, and engaging alumni, the community, and parents in the educational process to enhance support and participation. This research provides insights into the complexities and challenges of curriculum development in early childhood madrasas, as well as effective strategies to address them